Heroes of the Bible! Lions, shepherds and queens (oh, my!) - Vischer, Phil.; Botwick, Terry; Baykan, Bill.; Freeman, Gale.; Vischer, Lisa.; Nawrocki, Michael; Sage, Mike.; Olsen, Chris; Kaplan, Jennifer; Thomas, Pamela; Metaxes, Eric.; Jackson, Charlotte; et al. ([U.S.] : Big Idea : Distributed in the USA and Canada by Warner Home Video, 2002)
In "Daniel and the lion's den, " Larry the Cucumber (as Daniel) finds himself in deep trouble thanks to the King's conniving wisemen, played by a trio of slippery scallions. In an exciting finish, Daniel learns that even in the lion's den, he is still in God's hands. In "Dave and the giant pickle, " Junior Asparagus (as David) is pitted against a really mean, really big pickle! In the end, little Dave learns that it makes no difference whether you're 9-feet tall or 2-feet tall-- with God's help, even little guys can do big things. In "Esther, the girl who became queen, " a small-town girl wakes up with the weight of the world on her sholders and the fate of her people in her hands. Can she find the courage to do what's right?
Daniel and the lion's den / written and directed by Phil Vischer (c1998) -- Dave and the giant pickle / written and directed by Phil Vischer (c1996) -- Silly songs with Larry -- Esther, the girl who became queen / directed by Mike Nawrocki ; written by Phil Vischer, Mike Nawrocki ; produced by Jennifer Combs (c2000).
DVD release of the 2001 production.
Three episodes of the animated television show VeggieTales, created by Phil Vischer and Mike Nawrocki.
Bonus feature: 'Caught on tape' (outtakes of kids saying the funniest things about their favorite Bible heroes).
Gale Freeman, Lisa Vischer, Mike Nawrocki, Mike Sage, Phil Vischer, Chris Olsen, Jennifer Kaplan, Pamela Thomas, Eric Metaxes, Charlotte Jackson, Kristi Bramlet.
Esther: voices, Phil Vischer, Mike Nawrocki, Jennifer Kaplan, Pamela Thomas, Eric Metaxes, Charlotte Jackson, Kristi Bramlett.
Not rated.
Keywords: Daniel -- (Biblical figure) -- Fiction -- Juvenile films; David, -- King of Israel -- Fiction -- Juvenile films; Esther, -- Queen of Persia -- Fiction -- Juvenile films; Bible stories, English -- O. T. -- Fiction -- Juvenile films; Christian life -- Fiction -- Juvenile films; Video recordings for hard of hearing people; Children's films; Animated videos